ChemInform Abstract: Nano‐Sized Quaternary CuGa2In3S8 as an Efficient Photocatalyst for Solar Hydrogen Production. Issue 7 (29th January 2015) - Kandiel, Tarek A.; Anjum, Dalaver H.; Takanabe, Kazuhiro
Abstract Quaternary CuGa2In3S8 photocatalysts with a primary particle size of 4 nm are prepared by using a solution of Cu(acac)2, Ga(acac)3, In(acac)3, trioctylphosphine oxide, and oleylamine to which 1‐dodecanethiol is injected under Ar atmosphere (150 °C, aging at 285 °C for 2—24 h).